Bioremediation of diesel polluted soils with Eichhornia crassipes (water hyacinth) - Saheed I. MUSA; Felix M. OKE; Charlotte C. NDIRIBE (Notulae Scientia Biologicae, 2020)
Diesel oil contamination is a growing environmental concern in most crude oil processing regions of the world. This study assessed the efficacy of both fresh and powdered Eichhornia crassipes (water hyacinth) as potential biostimulants in the remediation of diesel oil contaminated soils using three test concentrations (50 g, 100 g and 150 g) and a control (0 g). The remediation process was monitored by assaying the total organic carbon (TOC), total petroleum hydrocarbon (TPH), and soil pH before and after amendment with the fresh and powdered E. crassipes for 90 days. The result showed increase in soil pH, TOC, TPH and volatile matter (VM) in comparison with the control due to soil contamination by diesel oil. However, there was a significant reduction (p < 0.05) in soil pH and TOC with the introduction of fresh and powdered E. crassipes at different concentrations. Contaminated soil amended with 100 g of fresh E. crassipes showed the highest TOC loss (59.7%) alongside soil amended with 100 g of powdered E. crassipes (47.36%) while the control showed the least TOC loss (0.91%). Similarly, soil TPH decreased significantly across all concentrations after amendment (p < 0.05). Overall, soil amended with fresh E. crassipes showed higher TPH loss than soil amended with powdered E. crassipes. This study reveals the potentials of using E. crassipes in the remediation of diesel oil contaminated soils. Above all, we demonstrate that fresh E. crassipes is a potentially stronger biostimulant than powdered E. crassipes.